Inflation, Corporate Income Taxation, and the Demand for Capital Assets - Kopcke, Richard W. (Journal of Political Economy, 1981)
The demand for capital is not systematically related to either the level or the rate of change of "effective" income tax rates on corporate capital assets. Rising inflation during the last 10 years has raised the user cost of capital for durable assets relative to that for short-lived assets even though this inflation has raised effective tax rates for more durable capital less than for short-lived assets. Even with replacement-cost depreciation allowances, the level and pattern of investment incentives probably will continue to vary with the inflation rate.